2004
DOI: 10.1515/jpm.2004.051
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine smoke exposure: a new risk factor for bronchopulmonary dysplasia?

Abstract: Prolonged mechanical ventilation, RDS and low gestational age were the major BPD determinants. Intrauterine smoke exposure seems to influence independently BPD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…This was mediated by down regulation of nicotinic receptors that in turn regulate other factors (hypoxia-inducible factor-1) involved in apoptosis control and angiogenesis in the developing fetal lung, which may explain the effects of ETS exposure on BPD [76]. In very low birth weight infants, intrauterine smoke exposure was also found to be an independent risk factor for BPD (OR 2.21; 95% CI 1.03–4.76) [77]. More recently, a case-control study looking at the respiratory outcomes of preterm infants with and without BPD exposed to both in utero smoking (IUS) and postnatal ETS showed that infants with BPD on home oxygen had the highest exposure to both [78].…”
Section: Resultsmentioning
confidence: 99%
“…This was mediated by down regulation of nicotinic receptors that in turn regulate other factors (hypoxia-inducible factor-1) involved in apoptosis control and angiogenesis in the developing fetal lung, which may explain the effects of ETS exposure on BPD [76]. In very low birth weight infants, intrauterine smoke exposure was also found to be an independent risk factor for BPD (OR 2.21; 95% CI 1.03–4.76) [77]. More recently, a case-control study looking at the respiratory outcomes of preterm infants with and without BPD exposed to both in utero smoking (IUS) and postnatal ETS showed that infants with BPD on home oxygen had the highest exposure to both [78].…”
Section: Resultsmentioning
confidence: 99%
“…Factors linked to BPD include: 1) low gestational age at birth (Kraybill et al, 1989;Darlow & Horwood, 1992;Antonucci et al, 2004;Ambalavanan & Novak, 2003), 2) low birth weight (Darlow & Horwood, 1992;Hakulinenet al, 1988;Avery et al, 1987;Ambalavanan et al, 2008), 3) growth restriction (small for gestational age) (Durrmeyer X et al, 2011;Lal Mk et al, 2003;Zeitlin J et al, 2010), 4) male sex (Kraybill et al, 1989;Darlow & Horwood, 1992;Ambalavanan & Novak, 2003;Avery et al, 1987), and 5) white race (Avery et al, 1987;Palta et al, 1991). In a recent cohort, BPD affected 85% of infants born at 22 weeks' gestation vs. 23% of those born at 28 weeks' (Stoll et al, 2010).…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Factors linked to BPD include: 1) low gestational age at birth Darlow & Horwood, 1992;Antonucci et al, 2004;Ambalavanan & Novak, 2003), 2) low birth weight (Darlow & Horwood, 1992;Hakulinenet al, 1988;Avery et al, 1987;Ambalavanan et al, 2008), 3) growth restriction (small for gestational age) (Durrmeyer X et al, 2011;Lal Mk et al, 2003;Zeitlin J et al, 2010), 4) male sex Darlow & Horwood, 1992;Ambalavanan & Novak, 2003;Avery et al, 1987), and 5) white race (Avery et al, 1987;Palta et al, 1991). In a recent cohort, BPD affected 85% of infants born at 22 weeks' gestation vs. 23% of those born at 28 weeks' (Stoll et al, 2010).…”
Section: Demographic Factorsmentioning
confidence: 99%